(untitled) (International Seven Journal of Multidisciplinary, 2023)
Limited Liability Companies (LLCs) have become one of the most commonly used business structures in the United States due to their operational flexibility and favorable tax treatment. This paper examines how LLCs are taxed under the U.S. Internal Revenue Code, focusing on income distribution mechanisms, mandatory filing requirements, and strategic tax planning. It also discusses the implications of regulatory updates such as the Corporate Transparency Act, which has imposed new reporting obligations for business entities. Key tax optimization strategies such as the Qualified Business Income (QBI) deduction, accelerated depreciation under Section 179, profit distribution planning, and S corporation election are explored with reference to academic and governmental sources. The study aims to equip entrepreneurs, tax professionals, and foreign investors with the tools to understand and leverage the LLC structure effectively while ensuring full compliance with IRS regulations.